Combatting negative bias: a mental contrasting and implementation intentions online intervention to increase help-seeking among individuals with elevated depressive symptomatology - Keeler, Amanda R.; Nydegger, Liesl A.; Crano, William D. (Frontiers in Psychology, 2023)
Background: There are many reasons why individuals with depression may not seek help. Among those with elevated depressive symptomatology, some previous interventions aimed at increasing help-seeking have unintentionally decreased help-seeking intentions. Beck’s cognitive theory of depression posits individuals with elevated depressive symptomatology process information differently from those without depression (i.e., increased cognitive errors, negative bias); potentially explaining the iatrogenic results of previous interventions. Mental contrasting and implementation intentions (MCII; a strategy using for advanced planning) interventions have successfully increased health behaviors–including mental health. However, MCII has not been used specifically for initiating help-seeking for depression. The goal of this research was to ascertain whether an online MCII intervention could increase actual help-seeking or the intention to seek help for depression. Method: Two online randomized pre-post experiments were conducted to measure the primary outcome measures two weeks post intervention (Study 1 collected Summer 2019: information-only control [“C”], help-seeking MCII intervention [“HS”], and comparison MCII intervention [“E”]; Study 2 collected Winter 2020: “C” and “HS”). At Time 1, adults recruited from MTurk had a minimum Beck Depression Inventory (BDI-II) score of 14 (mild depressive symptoms) and were not seeking professional help. Results: Study 1 (N=74) indicated that the intervention was feasible, provided preliminary support, and clarified intervention components for Study 2. Study 2 (N=224) indicated the HS group reported greater intentions to seek help and actual help-seeking compared to the C group. Proportionally, actual help-seeking was more likely among individuals who received the HS intervention and either did not perceive themselves as depressed at Time 2 or had BDI-II scores indicating that their depressive symptomatology decreased from Time 1. Limitations: Participation was limited to US residents who self-reported data. Discussion: These studies indicate that a brief online MCII intervention to encourage help-seeking is feasible and preliminarily successful. Future studies should consider using ecological momentary assessment measurements to establish temporal precedence of intervention effects and whether MCII is effective for encouraging help-seeking among individuals prone to experiencing cognitive errors who may not be experiencing negative bias (e.g., bipolar disorder or anxiety). Clinicians may find this method successful for encouraging ongoing treatment engagement.